Isolation and Characterization of Adipose-Derived Mesenchymal Stem Cell Exosomes: an In-Vitro Study - Jessica Fiolin; Ismail Hadisoebroto Dilogo; Radiana Dhewayani Antarianto; Ludwig Andre Pontoh (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Exosomes from Mesenchymal Stem Cells (MSC) is currently one of the highlighted research due to its more specific action on the target tissue. Exosome is one of the MSC Extracellular Vesicle (EVs) that acts as a mediator in the cellular communication. However, not so many literatures have succeed in elaborating its isolation and characterization process. This study aimed to explain the method used in exosomes isolation from Adipose-Derived MSC (ASC) and elaborate its characteristics. This is an in-vitro study performed in the Stem Cell and Tissue Engineering (SCTE) Indonesia Medical Education and Research Institute (IMERI) laboratory. Ultracentrifugation method was performed to isolate exosome from ASC. The exosome were characterized based on its particle size, morphology, and CD63 and CD81 expression for its purity. We were able to isolate sterile exosome from ASC by performing differential ultracentrifugation. The mean size of exosome was 88.7 nm ± 40 nm SD and showed expression of CD63 and CD81. Exosome was successfully isolated from ASC using ultracentrifugation method and characterization following the MISEV standard should be implemented in order to meet the therapeutic efficacy and safety issues as a regenerative agent.